Peripheral administration of blood from tau transgenic animals exacerbates brain tau-associated pathology - Vegas-Gómez, Laura; Pizarro, Matías; García-Martín, Jesús; Arredondo-Alcalá, María Ángeles; Bustamante, Bianca; González-Silva, Carolina; Matus, Soledad; Diaz-Espinoza, R.; Gutiérrez, Antonia; Morales, Rodrigo; Duran-Aniotz, Claudia; Moreno-González, Inés (Plos One, 2025)
The accumulation of amyloid plaques and neurofibrillary tangles are pathological hallmarks of Alzheimer’s disease (AD). While amyloid-beta propagation through prion-like mechanisms has been extensively studied in both central and peripheral pathways, the potential spreading of tau aggregates in the periphery remains largely unexplored. Emerging evidence suggests that hyperphosphorylated tau (ptau) aggregates may propagate beyond the central nervous system, as they have been detected in peripheral tissues and biological fluids from humans and mouse models of tauopathies. However, whether peripheral ptau aggregates or other factors associated to its accumulation contribute to brain pathology remains unclear. In this study, we investigate the contribution of peripheral blood from aged P301S tau transgenic mice to tau-associated brain pathology. Blood was administered via intraperitoneal and intravenous routes to assess their effect on cognitive and motor impairment, ptau accumulation, and glial response. Our findings reveal that inoculation of blood from aged P301S mice increases tau pathology in the hippocampus, exacerbates motor and cognitive impairment, and elevates glial response. These results underscore the potential role of peripheral factors in driving brain pathology, supporting the hypothesis that blood from affected individuals contributes to the progression of tau-related neurodegeneration. Elucidating the mechanisms of tau dissemination could provide critical insights into disease progression and strengthen the rationale for targeting tau as a therapeutic strategy in AD and other tauopathies.
Keywords: Alzheimer, Enfermedad de; Trastornos cognitivos; Amiloidosis; Alzheimer’s disease; Tauopathies; Tau aggregates; Prion-like propagation; Blood transfusion; Pathological seeds; Neurodegeneration; Cognitive impairment